2016
DOI: 10.1016/j.neubiorev.2016.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological signatures associated with alcohol and drug use in the human adolescent brain

Abstract: Magnetic resonance (MR) techniques provide opportunities to non-invasively characterize neurobiological milestones of adolescent brain development. Juxtaposed to the critical finalization of brain development is initiation of alcohol and substance use, and increased frequency and quantity of use, patterns that can lead to abuse and addiction. This review provides a comprehensive overview of existing MR studies of adolescent alcohol and drug users. The most common alteration reported across substance used and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 170 publications
(211 reference statements)
10
58
0
3
Order By: Relevance
“…The nature of vulnerability during this period of development highlights the critical role of experience in affecting neurodevelopmental trajectories throughout the lifespan. For example, previous research in animal models and humans have demonstrated that exposure to drugs of abuse during adolescence results in alterations in HPC volume and neurophysiology that has downstream consequences on drug abuse and affective disorders (see Spear, 2016 and Silveri et al, 2016 in the same issue), which may have downstream consequences on HPC-PFC interactions. Characterizing this period of adolescent development, and its sensitivity to drugs of abuse and other environmental insults, is critical to a greater understanding of normative increases in sensation seeking and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of vulnerability during this period of development highlights the critical role of experience in affecting neurodevelopmental trajectories throughout the lifespan. For example, previous research in animal models and humans have demonstrated that exposure to drugs of abuse during adolescence results in alterations in HPC volume and neurophysiology that has downstream consequences on drug abuse and affective disorders (see Spear, 2016 and Silveri et al, 2016 in the same issue), which may have downstream consequences on HPC-PFC interactions. Characterizing this period of adolescent development, and its sensitivity to drugs of abuse and other environmental insults, is critical to a greater understanding of normative increases in sensation seeking and psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Even the preference for a natural reward—sweet tastes—was found to be greater early in adolescence (11–15 years) than during late adolescence/emerging adulthood (19–25 years) (Desor and Beauchamp, 1987). A multitude of other studies have demonstrated enhanced sensitivity to rewarding stimuli in human adolescents for both decision-making/risk taking behaviors, as well as for cognitive control and learning behaviors, data that have been recently reviewed (see Andersen et al, 2002; and also in this issue: Luciana et al, 2016; Schulz and Sisk, 2016; Silveri et al, 2016; Spear, 2016; Vanderschuren et al, 2016; van Duijvenvoorde et al, 2016). …”
Section: Adolescent Sensitivity To Rewardsmentioning
confidence: 99%
“…Such propensities for alcohol/drug use during adolescence may not only be encouraged by an adolescent reward-sensitive phenotype, but also by (as we shall see) an attenuated sensitivity to aversive stimuli, including the aversive properties of alcohol, nicotine, and illicit drugs. This pattern of increased rewarding but decreased aversive sensitivities may help to promote high levels of alcohol/drug use among susceptible adolescents—elevated use that has the potential to impact normative developmental changes in brain structure and function during this critical period, thus altering neural processes and behaviors occurring within adolescence, as well as into adulthood (see reviews by Silveri et al, 2016 and Spear, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies, both preclinical (17, 18) and human (1921) show impaired WM integrity is associated with functional consequences, including impulsivity (19), decision making (22) and relapse (23). Importantly, emerging evidence implicates WM integrity across a range of psychiatric disorders and cognitive processes relevant to addiction (24, 25). Based on (1) modulation of cocaine cue reactivity in animal models via PPAR-γ agonism, and (2) evidence for neuroprotective effects of PPAR-γ agonism, we sought to identify analogous effects of PIO treatment in individuals with CUD.…”
Section: Introductionmentioning
confidence: 99%